1998
DOI: 10.1253/jcj.62.494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Early Stage of Carotid Atherosclerosis Using the Vascular Response to Nitroglycerin and High-Resolution Ultrasonography

Abstract: therosclerosis is a series of histopathological changes that includes intimal thickening, degenerative compositional changes of the medial layer (sclerotic change) and atheroma-formation (atherotic change). 1 The recent development of high-resolution Bmode ultrasonography has made it possible to detect and evaluate the atheromatous changes of the arteries, particulary the carotid artery. [2][3][4][5] However, despite these studies, methods that evaluate the sclerotic change of an artery, an early stage of athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The pre-HDBR responses to NG were consistent with previous research with an increase in heart rate (7), reduction in cardiac stroke volume (39), and lower arterial systolic, mean, and pulse pressure (22,38,39). A novel observation was the almost 50% reduction in femoral blood flow that reflected a marked reduction in downstream vascular conductance as demonstrated by the large reverse (negative) component, shown in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The pre-HDBR responses to NG were consistent with previous research with an increase in heart rate (7), reduction in cardiac stroke volume (39), and lower arterial systolic, mean, and pulse pressure (22,38,39). A novel observation was the almost 50% reduction in femoral blood flow that reflected a marked reduction in downstream vascular conductance as demonstrated by the large reverse (negative) component, shown in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…They concluded that the prevalence of carotid atheromatous plaque was highly correlated with that of CAD and that carotid vascular elasticity to GTN use was decreased in patients with severe CAD. 7 Their observation may support our theory that GTN causes less frequent headache in patients with atherosclerosis caused by impaired cerebral arterial dilatation. Adams et al 8 reported similar findings in 800 patients at risk for atherosclerosis.…”
Section: Discussionsupporting
confidence: 61%
“…We chose the carotid maximum IMT as a measurement device for evaluating 168 patients on long-term dialysis because of this method's proven efficacy as a predictor of generalized atherosclerosis. [10][11][12] Results from those prior investigations positively correlated carotid maximum IMT with age, and Dempsey et al calculated that age accounted for 17.7% of variation in carotid plaque thickness. 15 Kawagishi et al reported that in uremic patients the carotid maximum IMT related with age and that the rate of thickening was faster than in nonuremic controls.…”
Section: Discussionmentioning
confidence: 99%
“…8 Since the development of ultrasonography, accurate measurement of arterial intimal-medial thickness (IMT) has become feasible, 9 and IMT of the extracranial carotid arteries evaluated by Bmode ultrasonography is now used as a marker of systemic and coronary atherosclerosis. 10,11 This noninvasive, repeatable procedure makes it possible to measure atherosclerosis directly and quantitatively in a large asymptomatic population. B-mode ultrasound, therefore, is suitable for studying the relationship of multiple risk factors to arterial disease.…”
mentioning
confidence: 99%